Artificial Intelligence (AI) in Public Relations: Corporate Practices in Indonesia - Asep Soegiarto; Wina Puspita Sari; Abdul Kholik; Mentari Anugrah Imsa (International Journal of Social Science and Humanity, 2024)
The advancement of Artificial Intelligence (AI) has brought about significant changes in various industries, including public relations (PR) practices in companies. This research aims to explore the implementation of AI in corporate PR activities in Indonesia. Using a case study approach with in-depth interviews with PR practitioners from three major companies, this research reveals how AI is being used to optimise PR functions. The findings show that AI is primarily used to accelerate media and sentiment analysis, facilitate social media content management, and enhance personalisation and automation in marketing communications. However, there are still limitations to the implementation of AI due to resource constraints and regulatory factors. This research contributes to a better understanding of AI adoption in corporate PR practices in Indonesia and its future development potential. By examining real-world cases, it provides valuable insights into the opportunities and challenges associated with using AI for strategic communication efforts in an emerging market context.